PENEGAKAN HUKUM TERHADAP TINDAK PIDANA PERJUDIAN ONLINE - Fadhli, Muhammad (Indragiri Law Review, 2024)
Online gambling is becoming an increasingly prevalent phenomenon along with the development of technology and increasingly easy internet access. The crime of online gambling in Indonesia violates the legal regulations regulated in the Criminal Code (KUHP) and the Electronic Information and Transaction Law (ITE). Law enforcement against online gambling faces a number of challenges, including due to its cross-border nature and the use of advanced technology that makes it difficult to identify gambling site perpetrators and owners. This study aims to analyze the law enforcement mechanisms applied, both through preventive and repressive measures, as well as the role of related institutions, such as the police, the Prosecutor's Office, and Kominfo in overcoming this crime.